Rural-Urban Transition in Central Java: Population and Economic Structural Changes Based on Cluster Analysis - Handayani, Wiwandari (Land (Basel), 2013)
In Central Java, in addition to the traditional view of urban transition as an aspect of urban industrialization, rural industrialization based on small- to medium-sized enterprises has become a concern, at least since the Indonesian economic crisis in 1997. Combinations of typical urban and rural activities have resulted in certain features of rural-urban transition as the urban population has continued to increase notably. The intention of this paper is to examine how rural-urban transition characterizes the industrialization of Central Java. Multivariate cluster analysis is applied to create a typology, with the district as the unit of analysis, to better understand the transition phenomenon in terms of the population and economic structure. The cluster solution shows that rural-urban transition occurs on at least two different paths. The first path could be described as industrialization from above, in which the transition takes place as a part of the urban growth process. The second path could be described as industrialization from below, in which rapid industrialization occurs far from the highest hierarchy of the urban center.